SEBERAPA BESAR PARIWISATA MENDORONG EKONOMI? ANALISIS EMPIRIS TERHADAP PERTUMBUHAN PDB INDONESIA - Astriani Puspita Maharani; Catur Diah Ayu Putri Lestari; Deva Olivia; Fasya Febiani; Furkon Ardhani; Ahmad Setiawan Nuraya (Jurnal Pariwisata Tawangmangu, 2026)
The tourism sector plays a strategic role in Indonesia's economy as a source of foreign exchange earnings and employment, and a driver of GDP growth. However, increased tourism activity has not been fully followed by a stable increase in its contribution to national economic growth. This study uses a quantitative approach, employing quarterly time-series data for the period 2015Q1–2025Q4 (44 observations). Variables analyzed include GDP growth (Y), foreign-exchange tourism (X1), hotel occupancy rate (X2), and exchange rate (X3). Analysis was conducted using the Vector Error Correction Model (VECM), preceded by ADF stationarity tests and Johansen cointegration tests. The Johansen cointegration test confirms the existence of two long-run equilibrium relationships among the study variables. VECM estimation shows that tourism foreign exchange has a positive and significant effect on GDP growth in the long run (t-statistic = -6.9478), hotel occupancy rate also has a significant positive effect (t-statistic = -2.8341), while the exchange rate is not statistically significant (t-statistic = 0.1857). All three variables jointly show significant long-run relationships with GDP, as confirmed by the two Johansen cointegrating equations. The hotel occupancy rate is the most dominant and consistent variable driving Indonesia’s GDP growth, based on VECM estimation. Foreign exchange from tourism has a positive and significant long-run effect on GDP, consistent with the Tourism-Led Growth Hypothesis. The exchange rate has no significant effect at the 5% level due to inconsistent relationships during the COVID-19 pandemic.